Implementation of the Monetary Stage of Russian Privatization in 1997 - early 1998: Key Trends and Regional Specifics (on the Example of St. Petersburg) - T. V. Valov (Научный диалог)
The implementation of the monetary phase of Russian privatization in 1997 - early 1998 is discussed in the article. The relevance of the research is due to the fact that economic reforms and the privatization policy of the 1990s formed a socio-economic model and determined the characteristics of the political system of post-Soviet Russia, which led to the emergence of a number of basic problems facing Russian society in the late 2010s. It is noted that the post-communist transformation has become one of the most ambitious socio-economic shifts in the history of the 20th century. Therefore, according to the author of the article, it deserves a deep comprehensive study. The main trends in the privatization process of the 1990s are analyzed, the regional dimension is revealed on the example of St. Petersburg. The socio-political situation in the Russian Federation, which affects the course and dynamics of the transformation of property relations, is investigated. The government’s attempt to change the specifics of the privatization policy and further economic reforms in Russia is disclosed. The attention is paid to the political and criminal situation in St. Petersburg. The influence of privatization on the economy of the country, including the industry of St. Petersburg, is studied. The situation is considered on the example of a number of city enterprises. The social reaction to ongoing reforms is analyzed, in particular, the content of appeals of various public groups in connection with the implementation of the privatization policy.